Uniformity of working processes of jet and vortex ejectors, vortex tube and Hartmann–Sprenger pipe - V. I. Kuznetsov; V. V. Makarov (Омский научный вестник: Серия "Авиационно-ракетное и энергетическое машиностроение")
Based on the previously considered physical and mathematical models of jet and vortex ejectors, vortex tube and Hartmann–Sprenger tube, it makes a conclusion about the identity of the processes of exchange of work and heat in these devices. The influence of viscosity, tangential stresses, and the gradient of linear and angular velocities on the transfer of kinetic energy from a high-pressure to a low-pressure gas is shown. The difference of thermodynamic temperatures for heat exchange of high-pressure and low-pressure gases is taken into account.